Do psychosocial factors affect readmission in heart failure patients? A single centre study in a veteran population in south Florida, USA. (25th November 2020) - Mahabir, S; Kittipibul, V; Zarrabian, B; Alarcon-Calderon, A; Olarte, N; Marzouka, G; Palacio, A
Abstract: Background: We aim to determine the influence of psychosocial factors on readmission rates in a south Florida hospital serving a largely minority Veteran population with unique psychosocial co-morbidities that impact their health care. Purpose: We aim determine which psychosocial factors are predictors of readmission in patients with heart failure (HF). Methods: This is a retrospective study conducted at the Miami Veteran Affairs Medical Center (VAMC) in South Florida, USA. Patients who were admitted for heart failure exacerbations from September 2018 to August 2019 were identified and included in this study. Data on baseline charateristics and co-morbidities was obtained from review of patients' electronic health records. Psychosocial assessment was done via telephone interview using a previously validated questionnaire on gender, self-reported ethnicity, level of education, marital status, employment status, homelessness, monthly financial strain, overall stress level, neighbourhood safety and social interaction. Perceived health competence was assessed with the two items Perceived Health Competence Scale (PHCS-2). Results: We identified 185 patients during the study period (mean age 70.8±11.9 years, 98% male). Thirty-eight of these patients had one or more readmissions within one year. Our cohort was 22% White, 15% Hispanic and 60% African American based on self-reported race. We interviewed 78 patients; 14 with readmission, 64 without readmission. 21% had died at the time of our follow-up and we were unable to contact 27% of patients. On univariate analysis, homelessness and ejection fraction (LVEF) ≤40% were significantly associated with HF readmission (OR 8.3 p=0.002 and OR 6.8 p=0.008, respectively). No significant differences in other psychosocial characteristics were noted between groups. After adjustment for age in multivariate analysis, homelessness and LVEF <40% remained significant predictors for HF readmission (OR 13.4 p=0.005 and OR 8.8 p=0.02, respectively). Conclusions: Our study population was largely a minority population (15% Hispanic and 60% African American). After comparing multiple psychosocial factors, homelessness was found to be a significant and independent risk factor for heart failure readmission. This suggests that the recent focus on heart failure readmissions may need to include social interventions targeting homelessness. Future research should aim to determine whether multidisciplinary interventions aimed at addressing homelessness in patients with heart failure would help reduce hospital readmissions for congestive heart failure. Funding Acknowledgement: Type of funding source: None